2022
DOI: 10.1002/dev.22320
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood stress responses to psychosocial stressors: The state of the science

Abstract: The aim of this systematic review was to better understand whether and to what extent psychosocial stressors are associated with hypothalamic-pituitary-adrenal axis or autonomic nervous system stress responses in young children (1-6 years of age). Studies were classified by psychosocial stressors from the ecobiodevelopmental model: social and economic resources, maternal mental health, parent-child relationships, and the physical environment. Of the 2388 identified studies, 32 met full inclusion criteria, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…Researchers previously observed that chronic physiological stress is related to clinically diagnostic indicators of adverse mental health (Stalder et al, 2017; Steudte et al, 2011), but newer research finds no significant association, particularly between hair cortisol and major depressive disorder (Psarraki et al, 2021). Potential reasons for these conflicting results are confounding factors (Psarraki et al, 2021) and moderators of hair cortisol, including one's vast environmental context and intricate molecular dynamics that orchestrate unique stress responses (Bates et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers previously observed that chronic physiological stress is related to clinically diagnostic indicators of adverse mental health (Stalder et al, 2017; Steudte et al, 2011), but newer research finds no significant association, particularly between hair cortisol and major depressive disorder (Psarraki et al, 2021). Potential reasons for these conflicting results are confounding factors (Psarraki et al, 2021) and moderators of hair cortisol, including one's vast environmental context and intricate molecular dynamics that orchestrate unique stress responses (Bates et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, often missing from this conversation is the importance of understanding and addressing the effects of caregivers' mental health on young children (McGoron, 2023). While much research has documented the adverse effects of poor parent mental health on young children (Bates et al, 2022), investigations are emerging on the importance of mental health effects on children from another primary caregiver—early childhood educators (ECEs) (Hamre & Pianta, 2004; Hatfield et al, 2021; Neuenschwander et al, 2017; Whitaker et al, 2015). Indeed, ECEs may spend more awake time with many young children (0–5 years old) who attend early educational centers than the children's parents (including caregivers who act in the role of a parent).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hastings and colleagues (2021) followed a number of families throughout the first 9 months of the pandemic, demonstrating that the number of adverse changes in the family led to an increase in 4‐ to 5‐year‐old children's HCC. Moreover, a recent prospective study showed that family functioning predicted children's clinical symptoms of depression at the time of the COVID‐19 outbreak (Vacaru et al., 2022), and another revealed that parents reported more harsh parenting practices during the COVID‐19 pandemic (van den Heuvel et al., 2022), which may constitute a risk factor for children's heightened HCC (Bates et al., 2022; Windhorst et al., 2017). Lastly, caregiving quality is likely influenced by other factors, such as job loss and other pandemic‐related factors.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of clinically meaningful cortisol level cutoffs that indicate psychological stress 26 , 28 30 has traditionally made it difficult to categorize and compare patterns of lower or higher stress within dyads, regardless of the specimen used to measure cortisol (eg, hair, saliva, urine). Innovative methods such as latent mixture modeling, however, provide new opportunities to capture dyadic patterns even in the absence of established cutoffs.…”
Section: Introductionmentioning
confidence: 99%